Effect of Helicobacter pylori–induced gastric cancer on gastrointestinal microbiota: a narrative review - Heidary, Mohsen; Akrami, Sousan; Madanipour, Tohid; Shakib, Nafiseh Hosseinzadeh; Mahdizade Ari, Marzie; Beig, Masoumeh; Khoshnood, Saeed; Ghanavati, Roya; Bazdar, Monireh (Frontiers in Oncology, 2025)
Helicobacter pylori (H. pylori) infection is a typical microbial agent that interferes with the complex mechanisms of gastric homeostasis by disrupting the balance between the host gastric microbiota and mucosa-related factors, ultimately leading to inflammatory changes, dysbiosis, and gastric cancer (GC). We searched this field on the basis of PubMed, Google Scholar, Web of Science, and Scopus databases. Most studies show that H. pylori inhibits the colonization of other bacteria, resulting in a less variety of bacteria in the gastrointestinal (GI) tract. When comparing the patients with H. pylori–positive and H. pylori–negative GC, the composition of the gastric microbiome changes with increasing abundance of H. pylori (where present) in the gastritis stage, whereas, as the gastric carcinogenesis cascade progresses to GC, oral and intestinal-type pathogenic microbial strains predominate. H. pylori infection induces a premalignant milieu of atrophy and intestinal metaplasia, and the resulting change in gastric microbiota appears to play an important role in gastric carcinogenesis. The effect of H. pylori–induced GC on GI microbiota is discussed in this review.